Evolution of living standards in Romanian rural area during the COVID-19 pandemic - Geanina-Valentina Lupu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 11th Edition, 2020)
Throughout its history, Romania has gone through many crises in many sectors of the society. The premise, for the present situation, is that the reaction to a total crisis arising from a health problem, is being investigated. The consequences for the economy are still for analysis, but from now on they exceed the most pessimistic forecasts. The COVID -19 pandemic has consequences on the living standard of the population, especially if we consider the link between wage income fluctuations, gross domestic product, consumer price index in this period. All these indicators are analyzed and interpreted quantitatively and qualitatively based on data provided by the National Institute of Statistics, Eurostat and other institutions and organizations, which conducted studies between January and June 2020. This paper uses statistical data in order to highlight changes and effects on living standards in rural areas. In this sense, the economic, health, social measures adopted at national level are presented, with an emphasis on the impact for rural areas and the agricultural field. We consider in this sense, the decrease of the activity of certain sectors such as hotels and restaurants, tourism, transport, food, reduction of production, consumption, technical unemployment which has visible effects on the decrease of income of all, but especially on those in rural areas. All the factors presented increase the risk of poverty for the categories at the limit of this threshold and already affect negatively the standard of living for people living in rural areas.
Keywords: O15; J38; I38; P46; 330; health crisis; wage income; unemployment; poverty; rural areas